Development of an improved MMC-based fracture criterion characterizing the anisotropic and strain rate-dependent behavior of 6061-T5 aluminum alloy. (November 2020) - Ji, Cheng; Li, Zhigang; Liu, Jianguang
Abstract: Fracture behavior of aluminum alloy under complex loading conditions is of particular interest to researchers and practitioners. In this study, tensile tests were carried out on 6061-T5 aluminum alloy specimens at different stress triaxialities and Lode angles under different loading directions at various strain rates. The Hill48 yield criterion and a self-developed hardening model were combined to describe the anisotropic yielding and strain rate-dependent hardening behavior of 6061-T5 aluminum alloy. An improved MMC-based fracture model was developed to describe the anisotropic and strain rate-dependent fracture characteristics of 6061-T5 aluminum alloy and the parameters were calibrated by using a combined experimental-numerical approach. The improved MMC-based model was implemented into LS-DYNA as UMAT for the numerical simulation. By using the proposed fracture criterion, simulation results were highly consistent with experimental ones, which prove the reliability of the improved fracture criterion. Highlights: The anisotropic yielding and strain rate-dependent hardening behavior of Al6061-T5 were respectively represented. MMC fracture criterion was calibrated to represent the fracture behavior of Al6061-T5 at different stress states. An improved MMC-based model was developed to describe the anisotropic and rate-dependent fracture behavior of Al6061-T5. The improved MMC-based model was implemented into LS-DYNA as UMAT subroutine for simulation, which shows high accuracy.